Hadith #1384 - Sahih Muslim - Abi Asha'sha (Sahih Muslim)
While we were sitting with Abu Huraira in a mosque a man went out of the mosque after the call to prayer had been announced. (A man stood up in the mosque and set off.) Abu Huraira’s eyes followed him till he went out of the mosque. Upon this Abu Huraira said: This man has disobeyed Abu’l- Qasim (Muhammad) (ﷺ).
Grade: Sahih